Pakistan's Blasphemy Laws : From Islamic Empires to the Taliban - Abbas, Shemeem Burney (Book collections on Project MUSE., 2013)
Under the guise of Islamic law, the prophet Muhammad's Islam, and the Qur'an, states such as Pakistan, Afghanistan, Egypt, Saudi Arabia, and Bangladesh are using blasphemy laws to suppress freedom of speech. Yet the Prophet never tried or executed anyone for blasphemy, nor does the Qur'an authorize the practice. Asserting that blasphemy laws are neither Islamic nor Qur'anic, Shemeem Burney Abbas traces the evolution of these laws from the Islamic empires that followed the death of the Prophet Muhammad to the present-day Taliban. Her pathfinding study on the shari'a and gender demonstrates that Pakistan's blasphemy laws are the inventions of a military state that manipulates discourse in the name of Islam to exclude minorities, women, free thinkers, and even children from the rights of citizenship.